Effects of dynamic knee valgus alignment on ground reaction force and knee moment during landing - Wong, T.-L.; Chang, W.-C. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
This study examined the impact of dynamic knee valgus alignments on vertical ground reaction force(vGRF) and knee moment in 33 male collegiate athletes during a single-leg vertical jump from a 30-cm box. Categorized into valgus (n=12), neutral (n=8), and varus (n=13) groups based on knee angular displacement during landing, participants were analyzed 100 milliseconds immediately after initial ground contact. Normalized results indicate that the varus group demonstrated higher peak vGRF and maximum knee moment compared to the valgus and neutral groups. No significant differences were found in parameters like time to peak vGRF, loading rate, and peak hip moment. Our findings highlight the exacerbating effect of dynamic knee varus on landing impact, providing crucial insights for clinical applications and future research.